Natural plant hormones cytokinins increase stress resistance and longevity of Caenorhabditis elegans - Kadlecová, Alena; Jirsa, Tomáš; Novák, Ondřej; Kammenga, Jan; Strnad, Miroslav; Voller, Jiří (Biogerontology, 2018)
Cytokinins are phytohormones that are involved in many processes in plants, including growth, differentiation and leaf senescence. However, they also have various activities in animals. For example, kinetin and trans-zeatin can reduce levels of several aging markers in human fibroblasts. Kinetin can also protect mice against oxidative and glyoxidative stress, and prolong fruit flies' lifespan. Additionally, several cytokinins are currently used in cosmetics. To extend knowledge of the breadth of cytokinins' activities, we examined effects of natural cytokinin bases on the model nematode Caenorhabditis elegans. We found that kinetin, para-topolin and meta-topolin prolonged the lifespan of C. elegans. Kinetin also protected the organism against oxidative and heat stress. Furthermore, our results suggest that presence of reactive oxygen species, but not DAF-16 (the main effector of the insulin/insulin-like growth factor signaling pathway), is required for the beneficial effects of kinetin. Ultra-high performance liquid chromatography-tandem mass spectrometric analysis showed that kinetin is unlikely to occur naturally in C. elegans, but the worm efficiently absorbs and metabolizes it into kinetin riboside and kinetin riboside-5'-monophosphate.
Keywords: Insulin; reakce na tepelný šok; oxidační stres; Caenorhabditis elegans; Longevity; mutace; forkhead transkripční faktory; inzulin; termotolerance; dlouhověkost; reaktivní formy kyslíku; Kinetin; signální transdukce; regulátory růstu rostlin; Forkhead Transcription Factors; Cytokinins; Signal Transduction; Reactive Oxygen Species; cytokininy; Animals; Caenorhabditis elegans Proteins; Plant Growth Regulators; proteiny Caenorhabditis elegans; Heat-Shock Response; zvířata; Thermotolerance; Mutation; Oxidative Stress; kinetin